Conflitos pelo uso da água na bacia do Rio Claro e seus impactos na atividade agrícola - Paula, Cristiane Oliveira de (2014)
The Claro River is located in the State of Minas Gerais and is a major tributary of the Araguari River. Its basin covers an area of 1106.16 km ² belonging to the districts of Uberaba, Nova Ponte, Sacramento and Conquista. The headwaters of the Claro River and its originators are an important source for supplying the population of Uberaba, also its water supplies demands of agricultural crops irrigation, this region is a major producer of vegetables and grain. The basin of the Claro River underwent sweeping changes regarding use and land cover in recent decades. The increase in water demand for various purposes has led to a conflict over water use in this basin. In order to control the demand for water, the National Water Resources Policy, instituted by Law 9.433/1997, adopted the granting of right to use as an instrument to ensure the quantity, quality and regime of the resource. The award of grants is subject to water availability in the basin. The water availability in a basin is one of the most important information. It is usually estimated by reference of minimum flows, which represent the smallest flow rates of the historical series, and the drainage area is the most important variable for representation. Among the grants of right to use water issued in the basin of Claro River, the largest water demand is concentrated for irrigation and public supply in second, accounting for approximately 40% and 39% respectively. Besides the already installed conflict due to current uses, is in technical analysis by the competent organ, several applications for new grant funding. And there are still requests for environmental regularization of some small hydroelectric plants that strive to install in the source in study. With the implementation of these new uses, there may be an impact on agriculture in this region, which may diminish or even extinguish some food producing areas. In this sense, the present study aims to make a diagnosis of the basin, and from the relation between supply and demand of water of Claro River, make an assessment of the impacts on agricultural activity caused by the inclusion of other water uses.